2014
DOI: 10.1095/biolreprod.114.121434
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenesis in MA-10 Mouse Leydig Cells Is Altered via Fatty Acid Import into the Mitochondria1

Abstract: Mitochondria are home to many cellular processes, including oxidative phosphorylation and fatty acid metabolism, and in steroid-synthesizing cells, they are involved in cholesterol import and metabolism, which is the initiating step in steroidogenesis. The formation of macromolecular protein complexes aids in the regulation and efficiency of these mitochondrial functions, though because of their dynamic nature, they are hard to identify. To overcome this problem, we used Blue-Native PAGE with whole-gel mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…104 Each of these has an exclusive set of characteristics and applications, and can be synthesized by either conventional or unconventional methods. An extensive classification of NPs is provided in Figure 1 105–111Figure 1Different approaches to nanomaterial (NM) classification. Abbreviation: NPs, nanoparticles.…”
Section: Different Types Of Nanoparticlesmentioning
confidence: 99%
“…104 Each of these has an exclusive set of characteristics and applications, and can be synthesized by either conventional or unconventional methods. An extensive classification of NPs is provided in Figure 1 105–111Figure 1Different approaches to nanomaterial (NM) classification. Abbreviation: NPs, nanoparticles.…”
Section: Different Types Of Nanoparticlesmentioning
confidence: 99%
“…Incubation of primary cultures of rat Leydig cells in the presence of an activator of AMPK, resveratrol, decreases hCG-induced testosterone synthesis by inhibition of P450c17 and StAR ( 91 ). Moreover, it have been demonstrated that metformin decreases the capacity of Leydig cells to secrete progesterone ( 92 ). In rats and cows, the incubation of granulosa cells with metformin also induces a decline in steroid synthesis that is correlated with an increase in AMPK phosphorylation.…”
Section: Metformin and Steroidogenesismentioning
confidence: 99%
“…This finding strengthens the hypothesis that SCPX and SCP2 are involved in steroidogenesis, since Leydig cells are known to be the steroid-producing cells. Even though we recognize that there are huge differences between normal murine Leydig cells and the MA-10 mouse Leydig tumor cell line, the cell line was selected for further study of the subcellular distribution of SCPX and SCP2 because it is a well-established model to study the cellular and molecular mechanisms underlying hormone-dependent Leydig cell steroidogenesis [ 27 , 29 , 44 46 ]. Although not much work has been done concerning SCP2 in the MA-10 cell line, a previous study has used the MA-10 cells to study SCP2’s role in steroidogenesis, except that study focused on isolated mitochondria instead of entire cells [ 47 ].…”
Section: Discussionmentioning
confidence: 99%